Expression of the Thermobifida fusca xylanase Xyn11A in Pichia pastoris and its characterization - Zhao, Longmei (BMC Biotechnol, 2015)
BACKGROUND: Xylan is a major component of plant cells and the most abundant hemicellulose. Xylanases degrade xylan into monomers by randomly cleaving β-1,4-glycosidic bonds in the xylan backbone, and have widespread potential applications in various industries. The purpose of our study was to clone and express the endoxylanase gene xynA of Thermobifida fusca YX in its native form and with a C-terminal histidine (His) tag in Pichia pastoris X-33. We analyzed and compared these two forms of the protein and examined their potential applications in various industries. RESULTS: The xynA gene from T. fusca YX was successfully cloned and expressed using P. pastoris X-33. We produced a recombinant native form of the protein (rXyn11A) and a C-terminal His-tagged form of the desired protein (rXyn11A-(His)(6)). The specific activities of rXyn11A and rXyn11A-(His)(6) in culture supernatants approached 149.4 and 133.4 U/mg, respectively. These activities were approximately 4- and 3.5-fold higher than those for the non-recombinant wild-type Xyn11A (29.3 U/mg). Following purification, the specific activities of rXyn11A and rXyn11A-(His)(6) were 557.35 and 515.84 U/mg, respectively. The specific activity of rXyn11A was 8% higher than that of rXyn11A-(His)(6). Both recombinant xylanases were optimally active at 80°C and pH 8.0, and exhibited greater than 60% activity between pH 6–9 and 60–80°C. They exhibited similar pH stability, while rXyn11A exhibited better thermostability; N-glycosylation enhanced the thermostability of both recombinant xylanases. The products of beechwood xylan hydrolyzed by both xylanases included xylobiose, xylotriose, xylotetraose and xylopentaose. CONCLUSIONS: The C-terminal His tag had adverse effects when added to the Xyn11A protein. The thermostability of both recombinant xylanases was enhanced by N-glycosylation. Their stabilities at a high pH and temperature indicate their potential for application in various industries.